2020
DOI: 10.1108/jmlc-10-2019-0082
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of accountability in Nigeria: the role of deposit money bank

Abstract: Purpose The unhealthy drive for deposit in the banking sector has pushed many banks into unethical practices, thereby resulting in high-level corruption cases in the banking sector. The purpose of this study is to investigate the short- and long-run linkages between bank net interest income and deposit liabilities interacted with corruption, to establish the influence of corruption in deposit mobilisation drive of banks in Nigeria. Also, the study analysed the causal relationship between selected bank variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…By 2050, global population is expected to rise above 9 billion and this rise in World's population will no doubt increase the demand for food which will be driven by the hiked population and variations in climatic conditions in the coming decades. In West Africa, more than 35% of the total population is undernourished, which has contributed to the low life expectancy recorded in the sub-region Babajide et al, 2020).…”
Section: Literature Review and Conceptual Frameworkmentioning
confidence: 99%
“…By 2050, global population is expected to rise above 9 billion and this rise in World's population will no doubt increase the demand for food which will be driven by the hiked population and variations in climatic conditions in the coming decades. In West Africa, more than 35% of the total population is undernourished, which has contributed to the low life expectancy recorded in the sub-region Babajide et al, 2020).…”
Section: Literature Review and Conceptual Frameworkmentioning
confidence: 99%
“…Chen (2020) has also investigated bank profitability issues and stated that there is a relationship between loans and deposits and bank profitability; consequently, these items are also included in the current study. Apart from that, there is a large number of pieces of research investigating net interest income as a possible factor of profitability (Altavilla et al, 2018;Babajide et al, 2020;Borio et al, 2017). NaruÅ”evičius (2017) investigates the relationship between bank profitability and net commission income; hence, this indicator is studied in the current paper as well.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Aligning with the above submission, Taiwo and Agwu (2017) listed fraud and maintenance of e-banking as some of the challenges facing Nigeriaā€™s banking industry. Babajide et al (2020) reported that corporate fraud is prevalent in Nigeriaā€™s banking system and is often implicated in aiding corruption in collusion with politically exposed persons. There is also evidence that frauds occurrence may not be unconnected with governance problem within the Banking industry (Tade and Adeniyi, 2020) leading to the sack of five Board of directors of five Banks and injection of government funds in 2009 (Ribadu, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…There is also evidence that frauds occurrence may not be unconnected with governance problem within the Banking industry (Tade and Adeniyi, 2020) leading to the sack of five Board of directors of five Banks and injection of government funds in 2009 (Ribadu, 2016). According to Babajide et al (2020) frauds by bank management and staff retards bank growth and development and erodes profitability. It is against this background that this study examines nature of frauds and forgeries in Nigeriaā€™s cashless ecosystem, 2015ā€2019.…”
Section: Introductionmentioning
confidence: 99%